Droplet-on-demand platform for biochemical screening and drug discovery - Van,Vliet LD; Gielen,F; Sinha,A; Koprowski,BT; Edel,JB; Niu,X; De,Mello AJ; Hollfelder,F (2014)
We present new biochemical applications for an automated droplet screening system (the Mitos Dropix). This droplet-on-demand robotic platform was previously shown to perform automated dilution gradients that can be detected by absorbance or fluorescence in a time-resolved fashion without the need for a chip. We now present reproducibility data for the Dropix and show that it can be integrated with microfluidic devices to merge and split specific sequences of droplets. It can also be used to encapsulate cells and multi-cellular organisms.